1977
DOI: 10.1136/oem.34.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of Pesticides

Abstract: Book reviews those areas which the author regards as uncharted.This review will no doubt introduce the topic of shiftwork to a new and nationally wider circle of readers. It will certainly serve to underline to them the range and complexity of the problems involved, but they should not regard it as the final or latest word on the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The compounds of the classes of carbamates and dithiocarbamates with their chemical structures, use in agriculture, and maximum residue limit and toxic effect (Biscaldi et al, 1986;Cao et al, 2019;EPA, 1994aEPA, , 1994bEPA, , 1995EPA, , 1997EPA, , 1998EPA, , 2004bEPA, , 2004aEPA, , 2005bEPA, , 2005aEuropean Food Safety Authority, 2010; Food and Agriculture Organization of the United Nations & World Health Organization, 2020; Gupta, 2018;Gupta, 2006;Deshpande, 2002;Janz, 2014;McCarroll et al, 2002;Padilla et al, 2007;Park et al, 2021;Rodgers, 2001;Sams et al, 2010;Shibamoto & Bjeldanes, 2004;Union, 2020;Zhu et al, This class is composed of eight compounds, as shown in Table 1. These compounds were developed in the 1930s for applications during World War II as commercial fungicides for use in household products, in the treatment of ornamental plants, vegetables, crops, and seeds.…”
Section: Ta B L Ementioning
confidence: 99%
See 4 more Smart Citations
“…The compounds of the classes of carbamates and dithiocarbamates with their chemical structures, use in agriculture, and maximum residue limit and toxic effect (Biscaldi et al, 1986;Cao et al, 2019;EPA, 1994aEPA, , 1994bEPA, , 1995EPA, , 1997EPA, , 1998EPA, , 2004bEPA, , 2004aEPA, , 2005bEPA, , 2005aEuropean Food Safety Authority, 2010; Food and Agriculture Organization of the United Nations & World Health Organization, 2020; Gupta, 2018;Gupta, 2006;Deshpande, 2002;Janz, 2014;McCarroll et al, 2002;Padilla et al, 2007;Park et al, 2021;Rodgers, 2001;Sams et al, 2010;Shibamoto & Bjeldanes, 2004;Union, 2020;Zhu et al, This class is composed of eight compounds, as shown in Table 1. These compounds were developed in the 1930s for applications during World War II as commercial fungicides for use in household products, in the treatment of ornamental plants, vegetables, crops, and seeds.…”
Section: Ta B L Ementioning
confidence: 99%
“…These compounds were developed in the 1930s for applications during World War II as commercial fungicides for use in household products, in the treatment of ornamental plants, vegetables, crops, and seeds. Furthermore, some of these substances can have clinical applications, due to differences in the mode of actuation of biological activities of enzymes, proteins, and consequently, in their toxicity (Biscaldi et al, 1986;Janz, 2014;Krieger, 2011;Rubino et al, 2013;Szolar, 2007). However, the use of dithiocarbamates and the majority of carbamates was prohibited by the Codex Alimentarius, European Union (EU), and the United States due to their toxic effects.…”
Section: Ta B L Ementioning
confidence: 99%
See 3 more Smart Citations